Constitutional Status of Gilgit Baltistan: A Review of Historical, Legal, and Political Trajectories - Bashrat Hussain; Shoaib Malik; Muhammad Junaid; Asif Abbas; Nawaz Ali; Aamir Kaleem; Syed Murtaza Ali (Dialogue Social Science Review (DSSR), 2025)
GilgitBaltistan (GB) has remained a politically ambiguous region within Pakistan’s territorial landscape. This review synthesizes scholarly literature, government documents, and historical developments to explore the constitutional void that has governed GB’s status since 1947. Major themes discussed include the postcolonial governance model, legal disempowerment, ethnic identity concerns, and strategic economic dynamics. The paper compares governance approaches in GB and Azad Jammu & Kashmir and highlights critical gaps in policy. The review concludes with strategic recommendations aimed at resolving the longstanding constitutional limbo while balancing geopolitical and national integration concerns.